A survey on implementation of lightweight block ciphers for resource constraints devices. (4th July 2022) - Nayancy,; Dutta, Sandip; Chakraborty, Soubhik
Abstract: Lightweight cryptography is essential for securing resource-limited devices like smart card, RFID (radio-frequency identification)tags, sensor network and embedded system. In this paper, we present a survey of lightweight block ciphers from both software and hardware perspectives. This paper show the analysis of lightweight block ciphers on the basis of block size, key size, number of rounds, area in gate equivalent, speed, logic process as metrics for comparison purpose. Also, this comprehensive survey highlights the strengths and some of the security related issues in terms of key length and attacks in lightweight cryptography.